Abnormality of subcortical volume and resting functional connectivity in adolescents with early-onset and prodromal schizophrenia. (August 2021) - Wen, Dan; Wang, Junjie; Yao, Guanqun; Liu, Sha; Li, Xinrong; Li, Jing; Li, Hong; Xu, Yong
Abstract: Objective: Studies have found that there may be qualitative changes in brain structure and function in adolescents with early-onset schizophrenia (EOS) and prodromal schizophrenia (PDS). However, the abnormal brain structure and function of adolescents with EOS and PDS have received little attention, and their underlying neural mechanisms are still unknown. Methods: In this study, structural and resting-state functional magnetic resonance imaging (fMRI) were used to compare the subcortical volume and functional connectivity (FC) among EOS, PDS, and a control group. The Positive and Negative Symptom Scale (PNASS) questionnaire was used for clinical evaluation. Structural MRI was used to calculate cortical-based morphological volume and subcortical volume, and resting-state fMRI was used to analyze seed-based FC. Results: Structural MRI analyses showed that the gray matter volume of the hippocampus in EOS was significantly smaller than that in the control group, and the gray matter volume of the hippocampus, amygdala, and caudate nucleus in PDS was significantly smaller than that in the control group. Additionally, correlation analysis showed that the gray matter volume of the hippocampus was significantly negatively correlated with the negative symptom score of PANSS in EOS. When the hippocampus was used as the seed, fMRI analysis found that the FC between the hippocampus and the posterior cingulate gyrus and precuneus in EOS was significantly weaker than that in the control group. Conclusion: Our results indicate that the brain structure and function are abnormal in EOS and PDS, with abnormalities mainly concentrated in the limbic system, including the hippocampus, amygdala, caudate nucleus, cingulate gyrus, and precuneus. These findings provide a new direction for early intervention and improvement of the prognosis of schizophrenic patients.